Economics and the historian - Rawski, Thomas G. 1943-; Carter, Susan B.; Cohen, Jon S. 1939-; Cullenberg, Stephen 1953-; Lindert, Peter H. 1940-; McCloskey, Deirdre N. 1942-; Rockoff, Hugh 1945-; Sutch, Richard 1942-2019 (University of California Press, 1996)
These essays provide a thorough introduction to economics for historians. The authors, all eminent scholars, show how to use economic thinking, economic models, and economic methods to enrich historical research. They examine such vital issues as long-term trends, institutions, labor-including an engaging dialogue between a labor historian and a labor economist-international affairs, and money and banking. Scholars and teachers of history will welcome this volume as an introduction and guide to economics, a springboard for their own research, and a lively and provocative source of collateral r
Literaturverzeichnis Seite 253-278
Based on papers and discussions from the Workshop and Conference on Economic Methods for Chinese Historical Research held in Honolulu, Hawaii in January 1987 and Oracle, Arizona in January 1988
Keywords: Économie politique / Méthodologie; Historiographie; BUSINESS & ECONOMICS / Economics / General; BUSINESS & ECONOMICS / Reference; HISTORY / Historiography; Economics / Methodology; Historiography; Economische geschiedenis (wetenschap); Economie; Wirtschaftswissenschaften; Geschichtswissenschaft; Aufsatzsammlung; Wirtschaftstheorie; Geschichtsschreibung; Kongress; Wirtschaftsgeschichte (Fach); Wirtschaft; Economics -- Methodology; Wirtschaftsgeschichte -- Fach; Konferenzschrift -- 1987 -- Honolulu Hawaii